Financial development and economic growth in Poland 1990-2018 - Škare, Marinko; Sinković, Dean; Porada-Rochoń, Małgorzata (Technological and Economic Development of Economy, 2019)
The aim of the paper is to study finance-economic growth nexus in Poland using a time series approach. We find evidence of the existence of the finance-economic growth link in Poland.  Most empirical studies do not consider the lending structure of the financial sector (share of households’ vs firms in total credits). The obtained results show that when using the share of households and companies in total credits, the long run empirical relationship in VECM is statistically significant and larger. Empirical studies using total private credit share in the GDP or the value/volume of total credits tend to undervalue the impact of financial development on economic growth. In the case of Poland, empirical evidence that supports this hypothesis was found, and therefore policymakers and researchers should take bank lending structure into account. Furthermore, the study shows that financial series may possibly have long memory properties and that researching the financial development-growth nexus could require using fractional integration methods. The reported evidence suggests financial development plays a significant role in both economic growth and credit growth. Due to data limitation, this study focuses on a single country case – Poland with the need for further research (larger sample).